Bullying Behaviors in Children and Adolescents: “An Ongoing Story” - Tsitsika, Artemis K.; Barlou, Efi; Andrie, Elisabeth; Dimitropoulou, Christine; Tzavela, Eleni C.; Janikian, Mari; Tsolia, Marisa (Frontiers in Public Health, 2014)
Bullying is a universal problem which continues to be a serious threat to physical and emotional health of children and adolescents. This article highlights the prevalence, the common characteristics of bullies and victims, as well as the short- and long-term impact of bullying involvement. Key areas highlighted include the efficacy of bullying prevention programs, which can help health care providers to assess and provide interventions to children and adolescents affected by bullying.